AKSES TERHADAP ARSIP STATIS KATEGORI TERTUTUP: STUDI TERHADAP ARSIP PERISTIWA G 30 S/(PKI) YANG TERSIMPAN DI ANRI - Harry Bawono (Arsip Nasional Republik Indonesia, 2014)
This paper is focused on the description of the closed-access archive, particulary the one refers to the G 30 S / (PKI). Although, the policy to access certain archive have been endorsed for public, the grant to access the G 30 S / (PKI) is however still kept cryptic and restricted. The method used for this paper is literaure data collection, supported by interview. The results conclude that, since the G 30 S / (PKI) archives are classified as the repression archive and scrutinized by the grindle framework, the implementation gap of the access policy is morelikely originated from social-politics matter of contention than legal formal perspective